Correlates of health‐related quality of life in children with drug resistant epilepsy. (28th June 2016) - Conway, Lauryn; Smith, Mary Lou; Ferro, Mark A.; Speechley, Kathy N.; Connoly, Mary B.; Snead, O. Carter; Widjaja, Elysa
Summary: Objective: Health‐related quality of life (HRQL) is compromised in children with epilepsy. The current study aimed to identify correlates of HRQL in children with drug resistant epilepsy. Methods: Data came from 115 children enrolled in the Impact of Pediatric Epilepsy Surgery on Health‐Related Quality of Life Study (PEPSQOL), a multicenter prospective cohort study. Individual, clinical, and family factors were evaluated. HRQL was measured using the Quality of Life in Childhood Epilepsy Questionnaire (QOLCE), a parent‐rated epilepsy‐specific instrument, with composite scores ranging from 0 to 100. A series of univariable linear regression analyses were conducted to identify significant associations with HRQL, followed by a multivariable regression analysis. Results: Children had a mean age of 11.85 ± 3.81 years and 65 (56.5%) were male. The mean composite QOLCE score was 60.18 ± 16.69. Child age, sex, age at seizure onset, duration of epilepsy, caregiver age, caregiver education, and income were not significantly associated with HRQL. Univariable regression analyses revealed that a higher number of anti‐seizure medications (p = 0.020), lower IQ (p = 0.002), greater seizure frequency (p = 0.048), caregiver unemployment (p = 0.010), higher caregiver depressive and anxiety symptoms (p < 0.001 for both), poorer family adaptation, fewer family resources, and a greater number of family demands (p < 0.001 for all) were associated with lower HRQL. Multivariable regression analysis showed that lower child IQ (β = 0.20, p = 0.004), fewer family resources (β = 0.43, p = 0.012), and caregiver unemployment (β = 6.53, p = 0.018) were associated with diminished HRQL in children. Significance: The results emphasize the importance of child cognition and family variables in the HRQL of children with drug‐resistant epilepsy. The findings speak to the importance of offering comprehensive care to children and their families to address the nonmedical features that impact on HRQL.